Case Report and Review of Literature: Late Retrograde Type A Aortic Dissection With Rupture after Repair of Type B Aortic Dissection with a GORE TAG Endovascular Prosthesis - Manetta, Frank; Ajakaiye, Bayo; Scheinerman, S. Jacob; Yu, Pey-Jen (International Journal of Angiology, 2014)
Acute aortic dissection is the most common catastrophic condition of the aorta. Treatment options include open surgery and thoracic endovascular aortic reconstruction (TEVAR). We present a late Type A dissection as a complication of the management of descending aortic dissections with TEVAR and a review of the literature. TEVAR of the thoracic aorta is a viable treatment option for the management of complicated descending thoracic aortic dissections. Careful patient selection is necessary as medical therapy successfully treats the majority of uncomplicated Type B dissections. TEVAR should be reserved for patients with complicated Type B dissections or those who fail nonoperative management. Close postoperative monitoring is necessary when TEVAR is performed and should be accompanied by lifelong surveillance. A high level of suspicion is important to identify retrograde Type A dissections in these patients given its rarity and the ambiguity of its clinical presentation.
Keywords: aortic dissection; endograft placement; endograft repair; percutaneous; risk factors; stent